2004
DOI: 10.1002/path.1687
|View full text |Cite
|
Sign up to set email alerts
|

Systematic identification and molecular characterization of genes differentially expressed in breast and ovarian cancer

Abstract: The identification of novel disease-associated genes in gynaecological tumours has important implications for understanding the process of tumourigenesis and the development of novel treatment regimens. cDNA libraries from disease tissues may represent a valuable source to identify such genes. Recently, a bio-informatic procedure based on an 'electronic Northern' approach was established to screen expressed sequence tag (EST) libraries for genes differentially expressed in tumour and normal tissues, and identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 25 publications
6
45
1
Order By: Relevance
“…It has further been shown that malfunctions in nuclearcytoplasmic shuttling may contribute to carcinogenesis, for example, of breast and colon (Flamini et al, 1996;Lu et al, 2000). Therefore, the objective of this study was to unveil the potential phenotypical consequences of KPNA2 overexpression in vitro, as frequently found in breast cancer patients ex vivo (Dahl et al, 2005). As a prerequisite for such in depth functional characterization, gain-of-function models capable of overexpressing KPNA2 were required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has further been shown that malfunctions in nuclearcytoplasmic shuttling may contribute to carcinogenesis, for example, of breast and colon (Flamini et al, 1996;Lu et al, 2000). Therefore, the objective of this study was to unveil the potential phenotypical consequences of KPNA2 overexpression in vitro, as frequently found in breast cancer patients ex vivo (Dahl et al, 2005). As a prerequisite for such in depth functional characterization, gain-of-function models capable of overexpressing KPNA2 were required.…”
Section: Discussionmentioning
confidence: 99%
“…We previously discovered overexpression of KPNA2 mRNA in invasive breast cancer (Dahl et al, 2005), and subsequently demonstrated that breast cancer patients with increased nuclear KPNA2 protein expression in tumor cells presented advanced tumor size, poor tumor differentiation, reduced overall and recurrence-free survival (Dahl et al, 2006). Further gene expression studies revealed aberrant KPNA2 expression in premalignant and non-invasive ductal carcinomas in situ, indicating that this event occurs already in early stages of breast cancer development (Dankof et al, 2007;Klein et al, 2007).…”
mentioning
confidence: 97%
“…A clinical study of pancreatic ductal adenocarcinomas previously showed that high CapG expression was correlated with increased tumor size (Thompson et al, 2007a,b). Some researchers have reported that RNAi knockdown of CapG in human cancer cells, such as breast and pancreatic cancer cells can significantly reduce the invasion and motility of cancer cells and cell aggression (Dahl et al, 2005;Thompson et al, 2007a,b;Kang et al, 2010;Xu et al, 2010). CapG is considered to be a tumor promoter and can modulate invasive properties of cells during tumorigenesis (Veerle et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies (Kobayashi et al, 1995;Bourguignon et al, 1999;Paris et al, 2002;Zhang et al, 2004) have shown involvement of ITIs in tumour biology using an expressed sequence-tag-based bioinformatics approach (Dahl et al, 2005). We have previously identified ITIH5 as a novel gene differentially expressed in breast cancer.…”
Section: Introductionmentioning
confidence: 99%